Factors that influence sunscreen application thickness and potential preservative exposure. Issue 4 (5th April 2015) - Novick, Rachel; Anderson, Grace; Miller, Eric; Allgeier, Daniel; Unice, Ken
Summary Background/Purpose Studies have shown that individuals apply less than the 2 mg/cm2 lotion sunscreen needed to achieve the labeled SPF. However, there is little information regarding the application of spray and stick sunscreens. The objectives of this study were to measure the amount of sunscreen applied to skin by different application methods, to examine the relationship between application and demographic factors, and to evaluate the potential for sensitization from the preservative methylisothiazolinone (MI) in lotion sunscreens. Methods Fifty‐two participants applied lotion, spray, and stick sunscreen and answered a questionnaire. Lotion sunscreens were tested for MI content, and a margin of safety for the induction of skin sensitization was calculated. Results The geometric means for the application thickness of lotion, spray, and stick sunscreens were 1.1, 1.6, and 0.35 mg/cm2, respectively. Several factors influenced sunscreen application thickness, including age and skin type. The MI concentration in tested sunscreen lotions ranged from <1 to 5.6 ppm, and likely MI exposures were below the threshold for induction of allergy (margin of safety > 8.1). Conclusions In this study, sunscreen users applied different amounts of sunscreen depending on the application method, affording different levels of sun protection. Typical use of the sunscreens is not likely to result in MI sensitization.